Understanding the role of cutaneous allergy testing in anogenital dermatoses: a retrospective evaluation of contact sensitization in anogenital dermatoses. (6th February 2019) - Foley, Catherine C.; White, Siobhan; Merry, Subha; Nolan, Una; Moriarty, Blaithin; Kirby, Brian; Collins, Paul; Lally, Aoife
Abstract: Background: Patients with anogenital symptoms may delay before seeking medical attention. Attempted self‐treatment with multiple topical preparations and excessive hygiene measures offer ideal conditions for sensitization. The aim of this study was to identify the common allergens detected on cutaneous allergy testing in patients presenting with anogenital symptoms. Methods: A retrospective chart review of patients who underwent cutaneous allergy testing for perianal and/or genital symptoms over a 3‐year period, January 2013 to December 2015, n = 99. Information was gathered from medical records, pretesting questionnaires, and cutaneous allergy testing records. Results: At least one relevant allergen(s) was identified in 44/99 (45%) in our cohort, with allergic reactions to fragrances, Myroxylon pereirae, caine mix, sodium metabisulfite, and methylisothiazolinone most frequently observed. Conclusions: Cutaneous allergy testing is a useful investigation in patients presenting with anogenital symptoms, but advice regarding general skin care measures should not be omitted. The most commonly identified relevant allergens in our study were those present in over‐the‐counter cleansing and hemorrhoid preparations.